Quantum lattice learning and explainable artificial intelligence for maternal and child healthcare - Marvin, Ggaliwango (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2022.